PERAN JAMA’AH TABLIGH DALAM PEMBINAAN PENDIDIKAN AGAMA ISLAM PADA MASYARAKAT DESA TEMBORO KARAS MAGETAN - Futiati Romlah (Cendekia: Kependidikan dan Kemasyarakatan, 2011)
There are a number of religious guidance succeeded in building a good personality and character of Muslim conducted by a group or any particular religious stream. For instance, one of the groups is Jama’ah Tabligh of Temboro, Karas, Magetan. In line with this, it is necessary to learn in depth about this sort of group which is focused on the following issues: (1) the coaching forms of religious education and (2) the religious practice of the communities.  This study employed a qualitative descriptive approach through observation, interviews, and recording data as instruments. The results reveal that (1) the forms of religious education development are: (a) the activities of mosque community followed by elder and young men in the form of ubudiyah (call for prayer and congregation pray), daily meetings, hospitality, religious learning, lailatul ijtima’, maqomy recitation, and khuruj, (b) the activities of masturah followed by women and female teenagers involve religious family learning, weekly study groups, selapanan recitation, and three days out learning, and (c) Madrasah diniyah and tahfidzul Qur’an held by the community around the mosque without considering any age limitation, (2) The successful of religious education development is  reflected on the high awareness of the society, for instance to: (a) do daily worship, (b) prosper the mosque to worship and other activities, (c) educate the children with Islamic education and (d) use Islamic clothes. نجح كثير من الجماعات أو الفرق الإسلامية في تربية الناس المنتمين إليها تربية إسلامية، ومن هذه الجماعات " جماعة التبليغ" في تمبورو كارس ماغتان . أراد الباحث دراسة هذه الجماعة عميقة. وتكون الدراسة في نقطتين أساسيتين : هما (أ) صور عملية للتربية الدينية (ب) تطبيق العبادات والشعائر الدينية. فبأسلوب الملاحظة والمقابلة والمدخل الوصفي الكيفي حصل الباحث على النتائج التالية: (أ) إن التربية الدينية التي قام بها " جماعة التبليغ " هي (1) تطبيق صلاة  الجماعة في المسجد، يشترك فيها الأباء والأمهات والشبان والشابات و صلة الرحم والشورى والتعليم اليومي و الشهري (2) نشاط " المستورة " اشترك فيها الشبان والشابات ، وفيه تعليم ديني أسري، وتعليم أسبوعيّ ، وتعليم شهريّ و ارسال الدعاة لمدة 3 أيام (2) المحاضرة العامة و تحفيظ القران. اشترك فيها المجتمع عامة (ب) نجاح هذه التربية والأنشطة الدينية تظهر في وعي المجتمع (1) لأداء العبادات يوميا (2) وعمارة المساجد بالعبادات وغيرها (3) تربية الأولاد تربية إسلامية (5) والارتداء بلباس إسلامي.